Pengembangan Sistem Pakar Konsultasi Keuangan Pribadi Metode 50-30-20 Menggunakan Forward Chaining - Abdullah, Muhammad; Suprianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Effective personal financial planning is becoming increasingly important in the modern era. This study aims to develop a personal financial planning application based on an expert system that can assist individuals in making better financial decisions. The research methodology includes the 50-30-20 financial planning method, the forward chaining method for the inference engine, and the Expert System Development Life Cycle method for system development. System testing is conducted using the black box testing method. The research results show that the developed expert system successfully provides fund allocation recommendations that align with users' risk profiles and financial goals. This system not only accurately calculates the appropriate risk scale but also ensures that fund allocation adheres to sound financial principles. Black box testing also confirms that the system functions well and delivers accurate results. Thus, this expert system can serve as an effective tool for individuals in financial planning and achieving long-term financial goals. It has significant potential to enhance financial literacy in society and encourage prudent saving and investment behaviors. Keywords: Expert System, Forward Chaining, Black Box Testing, 50-30-20 Method, Financial Planning